Biomonitoring of the adult population living near the waste incinerator of Turin: Serum concentrations of PCDDs, PCDFs, and PCBs after three years from the plant start-up. (June 2021) - Iamiceli, AL; Abate, V; Abballe, A; Bena, A; De Filippis, SP; Dellatte, E; De Luca, S; Fulgenzi, AR; Iacovella, N; Ingelido, AM; Ivaldi, C; Marra, V; et al.
Abstract: In September 2013 a waste-to-energy (WTE) incinerator located in the Turin area (Piedmont, Northern Italy) started to produce energy by the incineration of municipal solid wastes. The plant, one of the largest WTE incinerator in Europe, burns up to 490, 000 tons of waste per year. A health surveillance program was implemented in order to evaluate the potential health effects on the population living near the plant. This program included a biomonitoring study aimed at assessing levels of several environmental contaminants including, among others, PCDDs, PCDFs, and PCBs. Before the WTE incinerator start-up (T0 ), a group of 85 subjects (41 "exposed" and 44 "not exposed" subjects) was randomly selected for enrollment by the local health units among individuals aged 36–50 years who had been living in the same area for at least five years prior to the study. Subjects were balanced by exposure area, sex and five-year age classes. As from the study design, the same cohort was re-evaluated after three years of incinerator activity (T2 ). A parallel study was conducted on a group of 12 farmers living and/or working in farms located in an area in the range of 5 km around the incinerator. Results of this study did not evidence any impact of the WTE plant on human exposure to PCDDs, PCDFs, and PCBs. In fact, no significant differences were found in the concentrations of PCDDs + PCDFs, DL-PCBs, and NDL-PCBs measured in the population group residing near the plant after three years of activity (T2 ) with respect to the control group. A significant decrease of serum concentrations of all the analytes was observed at T2 in both groups compared to T0 . Serum concentrations of PCDDs, PCDFs, and PCBs in the group of farmers were higher than those observed in the adult population under study. Graphical abstract: Image 1 Highlights: Human exposure to waste incinerator emissions is of great concern. No impact of the WTE plant was observed on human exposure to PCDDs, PCDFs, and PCBs. PCDD, PCDF and PCB decrease was observed at T2 in exposed and not exposed groups. Observed concentrations of PCDDs, PCDFs, and PCBs were higher in females.